Optimisation and validation of a remote monitoring system (Onco-TreC) for home-based management of oral anticancer therapies: an Italian multicentre feasibility study. Issue 5 (29th May 2017) - Passardi, Alessandro; Rizzo, Mimma; Maines, Francesca; Tondini, Carlo; Zambelli, Alberto; Vespignani, Roberto; Andreis, Daniele; Massa, Ilaria; Dianti, Marco; Forti, Stefano; Piras, Enrico Maria; Eccher, Claudio
Abstract : Introduction: Despite the growing number of oral agents available for cancer treatment, their efficacy may be reduced due to the lack of adherence, inappropriate adverse event self-management and arbitrary dose adjustment. The management of anticancer therapies could exponentially benefit from the introduction of mobile health technologies in a highly integrated electronic oncology system. Methods and analysis: We plan to customise and fine-tune an existing monitoring TreC platform used in different chronic diseases in the oncology setting. This project follows a multistep approach with two major purposes: 1. participatory design techniques driven by Health Literacy and Patient Reported Outcomes principles in order to adapt the system to the oncology setting involving patients and healthcare providers; 2. a prospective training-validation, interventional, non-pharmacological, multicentre study on a series of consecutive patients with cancer (20 and 60 patients in the training and validation steps, respectively) in order to assess system capability, usability and acceptability. The novel Onco-TreC 2.0 is expected to contribute to improving the adherence and safety of cancer care, promoting patient empowerment and patient–doctor communication. Ethics and dissemination: Ethical approval was obtained from the Independent Ethics Committees of the participating institutions (CEIIAV protocol Number 2549/2015; reference Number 1315-PU). Informed consent will be obtained from all study participants. Findings will be disseminated through peer-reviewed journals, conferences and event presentations. Trial registration number: ClinicalTrials.gov (NCT02921724 ); (Pre-results). Other study ID Number: IRST100.18.